2017
DOI: 10.3389/fmars.2017.00397
|View full text |Cite
|
Sign up to set email alerts
|

Biosilicification Drives a Decline of Dissolved Si in the Oceans through Geologic Time

Abstract: Biosilicification has driven variation in the global Si cycle over geologic time. The evolution of different eukaryotic lineages that convert dissolved Si (DSi) into mineralized structures (higher plants, siliceous sponges, radiolarians, and diatoms) has driven a secular decrease in DSi in the global ocean leading to the low DSi concentrations seen today. Recent studies, however, have questioned the timing previously proposed for the DSi decreases and the concentration changes through deep time, which would ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 172 publications
(297 reference statements)
4
90
0
Order By: Relevance
“…Diatoms were likely key players in the ocean Si cycle in the Early Cenozoic (Conley et al, 2017; Renaudie et al, 2018), so we can use insights from the modern ocean to guide our interpretations. Today, sea surface δ 30 Si is primarily driven by diatom Si uptake and precipitation of their frustules.…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms were likely key players in the ocean Si cycle in the Early Cenozoic (Conley et al, 2017; Renaudie et al, 2018), so we can use insights from the modern ocean to guide our interpretations. Today, sea surface δ 30 Si is primarily driven by diatom Si uptake and precipitation of their frustules.…”
Section: Discussionmentioning
confidence: 99%
“…The global silicon (Si) cycle is of great interest due to the role that silicate weathering has played in maintaining climatic stability on geological time scales (Siever, 1991;Frings et al, 2016;Conley et al, 2017) and because Si is an important nutrient for many organisms in marine and freshwater ecosystems. It occurs as silicate minerals in association with all rock types (igneous, metamorphic, sedimentary).…”
Section: Introductionmentioning
confidence: 99%
“…Weathering, biological and geochemical transformations, transport and interactions with other elements (in particular nutrients and carbon) form the basis of the global biogeochemical Si cycle . The global Si cycle has evolved through geologic time with overall declines in oceanic dissolved Si due to the uptake and deposition by organisms (Siever, 1991;Conley et al, 2017). While the modern Si biogeochemical cycle is influenced by anthropogenic forcing (Laruelle et al, 2009), the processes of weathering and burial as biogenic silica (bSiO 2 ) are the dominant processes in the biogeochemical Si cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have robustly demonstrated the presence of very low oceanic silicic acid concentrations since at least 60 Ma, most likely as a result of the drawdown of silicic acid by diatom biomineralization (Fontorbe et al, 2016, which is tens of millions of years before the time period envisioned by Siever (1991) and others. Conley et al (2017) have hypothesized that if such a global decrease in oceanic silicic acid concentrations Sims et al, 2006;Fontorbe et al, 2016Fontorbe et al, , 2017 Diatoms and sponges Post-Mesozoic decline of certain sponge spicule morphologies Maldonado et al, 1999 Diatoms and radiolarians; Diatoms and silicoflagellates Silicificaton and shell-thickness/spine morphology, decline of radiolarians in the low latitudes throughout the Cenozoic (reason still debated) Lazarus et al, 2009;van Tol et al, 2012;Cermeño et al, 2015 Ecology in modern oceans…”
Section: Evolutionary Competition Across Geological Timementioning
confidence: 99%
“…The nature of this competition has changed over geological time in conjunction with changes in the biogeochemical cycling of silicon (Racki and Cordey, 2000;Maliva et al, 2005;Finkel and Kotrc, 2010;Knoll and Kotrc, 2015;Conley et al, 2017). In turn, this is reflected in the evolutionary molecular biology of silicon transport mechanisms.…”
Section: Cellular and Molecular Aspects Of Evolutionary Competitionmentioning
confidence: 99%